2015
DOI: 10.1186/s12909-015-0431-1
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly research productivity is not related to higher three-year licensure pass rates for physical therapy academic programs

Abstract: BackgroundIn the domain of academia, the scholarship of research may include, but not limited to, peer-reviewed publications, presentations, or grant submissions. Programmatic research productivity is one of many measures of academic program reputation and ranking. Another measure or tool for quantifying learning success among physical therapists education programs in the USA is 100 % three year pass rates of graduates on the standardized National Physical Therapy Examination (NPTE). In this study, we endeavor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…23 However, very few metrics are collected and monitored by all academic programs beyond those required by the accrediting body. Although AAR data gathered and shared by CAPTE 20 have been valuable in addressing specific questions in academic PT, [24][25][26][27] the data address the minimum requirements for accreditation. Details on the learning experience and program processes remain limited, 24 briefly described, and housed within individual programs' self-studies and not publicly available.…”
Section: The Current State Of Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, very few metrics are collected and monitored by all academic programs beyond those required by the accrediting body. Although AAR data gathered and shared by CAPTE 20 have been valuable in addressing specific questions in academic PT, [24][25][26][27] the data address the minimum requirements for accreditation. Details on the learning experience and program processes remain limited, 24 briefly described, and housed within individual programs' self-studies and not publicly available.…”
Section: The Current State Of Data Availabilitymentioning
confidence: 99%
“…Although AAR data gathered and shared by CAPTE 20 have been valuable in addressing specific questions in academic PT, [24][25][26][27] the data address the minimum requirements for accreditation. Details on the learning experience and program processes remain limited, 24 briefly described, and housed within individual programs' self-studies and not publicly available. In addition, although program costs, graduation rate, and licensure rate must be shared on individual program Web sites, there is no efficient process or data system by which a program may view aggregated national data beyond that collected by CAPTE.…”
Section: The Current State Of Data Availabilitymentioning
confidence: 99%
“…It has also been shown that Physical Therapy faculty research productivity does not correlate with their students' academic success when controlling for number of faculty, student undergraduate GPA and demographic profile, among other factors (Cook et al 2015). A possible interpretation of these results is that faculty research productivity contributes substantially to a sense of prestige for the program or institution but does not materially benefit Physical Therapy student learning or outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…CAPTE requires a minimum standard for scholarship for faculty within a DPT program that at least 50% of a program's core faculty hold an advanced academic doctoral degree beyond a clinically-based DPT [5]. Beyond CAPTE, scholarly activity is a common program requirement for all academic faculty members used to determine the qualitative strength and ranking of a program [6][7][8][9][10][11]. Scholarly activity refers to much more than traditional research.…”
Section: Introductionmentioning
confidence: 99%
“…Scholarly activity is historically low among physical therapy programs [6], although a program's level of productivity does not seem to influence a program's National Physical Therapy Examination (NPTE) pass rate in a recent study [7]. To date, the NPTE pass rates are most notably influenced by student-level factors such as mean undergraduate GPA [10].…”
Section: Introductionmentioning
confidence: 99%